(untitled) (AYUSHDHARA, 2024)
The incredible journey of Ayurveda from its holy beginnings to the present has us contemplating the immense potential that this science holds. Its successful existence since time immemorial itself proves its scientific approach attributed to its unique basic principles that remain unchanged. The theory of Ritu and Ritusandhi has been acknowledged as a fundamental principle and it is a specific causative factor to occur all the type of diseases. As the human body has a circadian rhythm and biological clock, they have an impact on every facet of human physiology. Vagbhatta describes Ritusandhi, at the end of Ritucharya. Ritu means season while Sandhi is the junction or meeting of two things. This indicates that Ritusandhi is where two Ritu converge. Ritusandhi is the sum of the last seven days of the just concluded season and the first seven days of the next or current season, which is about to start. As a result, the 14-day span that separates the conclusion of two distinct seasons. Since a person’s health depends on their surroundings, it is also crucial to protect them from the elements throughout the transitional seasons. These seasonal changes weaken the body’s immune system and create an environment that is conducive to the spread of illness. In order to improve our eating habits and daily routine and prevent Sandhi Kalagat disease, we must be aware of the preventative aspects of Ritusandhi (for example allergic diseases, urticaria, conjunctivitis, viral fever, cold, cough etc.) Since maintaining one’s health, or "Swasthya rakshan," is the primary objective of Ayurveda, the significance of Ritusandhi is emphasized in this review article.